Editorial: 50th anniversary of FEPSAC - Strauss, B.; Ntoumanis, Nikos (ELSEVIER SCIENCE BV, 2019)
In 1969, 50 years ago, FEPSAC (European Federation of Sport Psychology) was founded in Vittel (France) during the 2nd European Congress of Sport Psychology; the first European Congress took place 1968 in Varna (Bulgaria). This year FEPSAC celebrates its 50th anniversary during the 15th European Congress of Sport and Exercise Psychology in Muenster (Germany).